Epidemiology of Adenomyosis - Upson, Kristen; Missmer, Stacey A. (Seminars in Reproductive Medicine, 2020)
Adenomyosis, characterized by the presence of endometrial glands and stroma within the myometrium, can have a substantial impact on the quality of women's lives. Despite this, the epidemiologic research on this condition lags considerably behind that of other noncancerous reproductive health conditions. The lack of progress and knowledge is due in part to the challenges in designing valid epidemiologic studies, since the diagnosis of adenomyosis historically has been limited to the examination of uterine specimens from hysterectomy. This review describes the available data on the frequency of this condition and the epidemiologic investigation thus far into the risk factors for disease—highlighting the methodologic and inference challenges primarily around study sample selection. We conclude with providing recommendations for approaches to future epidemiologic study that capitalize on the advancements in imaging technology to detect adenomyosis and provide a fuller picture of the occurrence and risk factors for disease.
Keywords: adenomyosis; epidemiology; risk factors; prevalence; hysterectomy